VR VanMieu: The Interactively Virtual Temple of Literature - Dinh, Ngoc Van (Springer Nature, 2023)
Lecture Notes in Networks and Systems (LNNS, volume 734); CITA: Conference on Information Technology and its Applications; pp: 274-284.